Cytomorphological evaluation of synovial lesions in a tertiary care centre in North India: A retrospective study - Poonam Sharma; Rajat Gupta; Subhash Bhardwaj; Manik Mahajan (Journal of Cytology, 2020)
Background: Numerous pathological processes involve synovium and periarticular tissues that are characteristic and in some cases specific to a particular disease. Synovial fluid is a thick, stringy fluid found in the cavity of synovial joint. Examination of the synovium plays a key role in the diagnosis of many joint diseases. Aims: The aim of this study was to study the spectrum of synovial lesions on fine needle aspiration cytology (FNAC) and to compare the cytological diagnosis with histopathological findings. Material and Methods: This retrospective diagnostic analytical study was carried out in the Department of Pathology. Sixty-six patients with suspected synovial lesions referred from other departments who underwent FNAC during 1 year from January 2017 to December 2017 were included in the study. The slides along with records of the patients were retrieved and findings recorded. Histopathological evaluation was performed wherever possible and compared with cytological diagnosis. Results: Non-neoplastic lesions accounted for 80.3% cases followed by benign tumors (15.2%). Ganglion cyst was the commonest non-neoplastic lesion (60.6%, 40/66), while tenosynovial giant cell tumor was the commonest neoplasm (12.1%, 8/66) observed in our study. Solitary case of synovial sarcoma was also observed. Histopathological evaluation was performed in 14 cases and FNAC had overall diagnostic accuracy of 85.7% in diagnosis of these lesions. Conclusions: FNAC is a useful tool with high diagnostic accuracy in the evaluation of synovial lesions.